Breaking the barriers: understanding employer reluctance to hire former drug addicts in Malaysia - Mohamad Murad, Nurfatin Afza; Mohd Khir, Azlina; Ma'rof, Aini Azeqa; Wan Jaafar, Wan Munira (Human Resources Management Academic Research Society (HRMARS), 2024)
This work aims at establishing why Malaysian employers have not been willing to employ those who used to be drug addicts. Three main obstacles are identified by the research through in-depth qualitative interviews with employers from different industries: fear of stigma, concerns with reliability and safety at the workplace, and nonexistence of favorable environments or regulations. This is primarily because of prejudice and fears about slipping that so often render ex drug addicts as untamed or untrustworthy employees among employers. Employers are also dissuaded from considering ex-addicts because they also feel incompetent to cause prevention risks without institutional support even when there are no stated policies or incentives. The truth is that while some companies gladly declare that they participate in recruitment of people who have undertaken rehabilitation, they are ready to accept such a subject only if he has documents which will testify about his successful passing and guarantees that he will be given further help. The outcomes imply the need to organize specific efforts aimed at eradicating such barriers. Educational programs of the employer are necessary to combat stereotypes and increase public awareness of what can be done by persons who rebuilt their lives after addiction. Additionally, modifications in policies where either taxes or law protect firms could reduce bias in hiring a diverse workforce even more. Also, programs of certification particularly when the rehabilitation is successful and institutions for support when hiring newly reformed employees would reassure businesses of the reliability of employees who have been through drug addiction. The report includes a detailed action plan which implies improving drug addicts’ employment rates which, in its turn, helps them to be socially resumed and reduces a number of people who go back to drug consuming. It does this by dealing with the issues of stigmatization and institutional decline pertinent to this subject. These tactics may likely enhance a diverse and better pool of human resources in Malaysia.